Rancang Aplikasi Smarthome Menggunakan Rapid Application Development Berbasis Hybird Mobile - Desy Agustin; Alkautsar Permana; Muchamad Taufiq Anwar; Laksmi Ambarwati (Jurnal Teknologi Informasi dan Pendidikan, 2023)
Information technology and computing technology are currently being developed simultaneously to be able to provide information that is processed automatically so as to provide a system that can be used to facilitate human activities. Currently, the smart home is a technology that continues to be improved, such as speed and accuracy in the process inside. This study aims to design a Smart Home application that uses the basic concept of the Internet of Things (IOT) using the Hybrid Mobile-based Rapid application development (RAD) method. The Rapid Application Development (RAD) method focuses on developing an application quickly, precisely and adaptively. By using the RAD method, the smart home application can be applied to Hybrid Mobile where the condition of some electrical equipment in the house can be controlled remotely, namely using a smartphone application or WEB application. From the results of this study the system can monitor and control several electrical equipment at home using the button command feature on mobile and web applications.